Growth, single crystal investigations, Hirshfeld surface analysis, DFT studies, molecular dynamics simulations, molecular docking, physico-chemical characterization and biological activity of novel thiocyanic complex with zinc transition metal precursor. (1st August 2022) - Makhlouf, Jawher; El Bakri, Youness; Valkonen, Arto; Saravanan, Kandasamy; Ahmad, Sajjad; Smirani, Wajda
Graphical abstract: Highlights: An effective biological property is observed for the compound. A high stabilization energy from metal to ligand confirmed the NLO activity for Zn-metal complex. The enzyme revealed several key active site residues to form short distance hydrophilic and hydrophobic contacts with the compound. Abstract: The present work undertakes the study of novel thiocyanic complex, which have been obtained due to the interaction of cationic entities with the thiocyanate ligands. In fact, these latter are added to a transition metal leading to the production of novel solid-state complex that was studied and characterized by single crystal X-ray crystallography. However, (C11 H18 N2 O)[Zn(SCN)4 ] crystallizes in orthorhombic system with the non-centrosymmetric space group P 21 21 21, with the following lattice parameters: a = 8.4726(2) Å, b = 14.6043 (7) Å, c = 17.1927 (14) Å with V = 2127.3 (14) Å 3 and Z = 4. Infrared spectrum was registered to revel the vibrational modes of the compound, add to the study of the optical properties using a polar solvent to carry out the UV–visible analysis. Thermogravimetric analysis techniques (TGA) and thermo-differential analysis techniques (DTA) were carried out to account for the thermal decomposition of complex. Furthermore, the antibacterial properties were determined against some bacteria. In order to gain insights into the role of weak molecular interactions in the complex that influence the self-assembly process and crystal packing, Hirshfeld surface analysis and DFT calculation were also performed. Furthermore, molecular docking and molecular dynamic simulations were performed for the compound against different antibacterial targets to identify to which target the compound show the best binding affinity. The MurF enzyme, which catalyzed the last cytoplasmic step of bacterial peptidoglycan synthesis, among the target was revealed to show better interactions with the enzyme and formed strong and stable intermolecular complex.